Needs Analysis to Develop Static Fluid E-Student Worksheet Integrated Problem Based Learning and Local Wisdom to Facilitate Students’ Physics Learning Outcomes - Miftah Hurrahmah; Hidayati Hidayati; Fatni Mufit; Hayyu Yumna (Universitas Negeri Padang, 2026)
This research is motivated by the low cognitive learning outcomes of students in physics learning, especially the static fluid material. This problem shows that the learning process has not been fully able to facilitate active involvement and optimal understanding of concepts. This study aims to analyze learning needs as the basis for the development of Problem-Based Learning (PBL)-based E-Student Worksheets that are oriented towards local wisdom to improve students' cognitive learning outcomes. This research constitutes the Define stage of the 4D development model. The research subjects consisted of physics teachers and Grade XI students at SMAN 9 Mandau. Data collection techniques included questionnaires, interviews, and document analysis. The data were analyzed using a qualitative descriptive approach. The results of the study show that the cognitive learning outcomes of students in the static fluid material are still relatively low. The discussion of the results revealed that these achievements were influenced by the use of teaching materials that were not optimal in facilitating the active involvement of students, as well as the lack of material linkage with local wisdom phenomena in the surrounding environment. On the other hand, students have potential in the form of digital readiness and technological literacy that supports electronic-based learning. Based on these findings, it is concluded that the development of PBL-based E-Student Worksheets that integrate local wisdom is needed as an innovative solution to create more contextual and interactive learning that optimizes students' cognitive learning outcomes.